Development and Characterization of Phytoconstituent Loaded Niosomal Formulation as Targeted Delivery System in Breast Cancer Treatment - Chaudhari, Shilpa P.; Sharma, Ruchi (Journal of Neonatal Surgery, 2025)
The present work aims to comprehensively examine and analyze Niosomal formulations, with a special focus on their potential use as a targeted delivery approach for the treatment of breast cancer. The objective of this study is to get in-depth understanding of the dynamic field of cancer therapeutics by conducting a thorough examination of formulation parameters and characterization techniques. The research aims to address the pressing need for novel treatment options in light of breast cancer's increasing prevalence and impact on women's health in India. This disease has now surpassed cervical cancer as a major cause of morbidity and death among women in the country. Niosomes, which are vesicles composed of lipids, have shown the capacity to augment the sustained release of drugs, so enabling a controlled and prolonged therapeutic effect. By using the mechanism of endocytosis, these formulations effectively promote the internalization of medicines into cellular structures, so permitting precise delivery to specific intracellular locations. The investigation of niosomal formulations as precise delivery methods in the context of breast cancer treatment signifies a notable development in the field of cancer therapies. Niosomes has distinctive characteristics that render them very promising vehicles for drug delivery, since they have the capacity to be customized for precise targeting of cancer cells while minimizing detrimental impacts on healthy organs. Therefore, the use of niosomal formulations as a precise delivery strategy in the treatment of breast cancer has potential in enhancing the therapeutic efficacy of anticancer medications while mitigating undesired adverse reactions. Ongoing scholarly research activities are focused on further investigating and improving these formulations, with the objective of maximizing their efficacy in clinical environments.